Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

A review on sustainable aviation fuel production via diverse biomass and waste-derived feedstocks and cutting-edge conversion technologies - Wajahat Waheed Kazmi; Muhammad Wasi Syed; Muhammad Waqas; Umair Hassan Bhatti; Ahmed Omer; Mansoor Ali; Zulqarnain; Ishaq Kariim; Amjad Hussain; Faysal M. Al-Khulaifi (Biomass and Bioenergy, 2026)

Rock–water interactions in the coal mining area of Dukki, Balochistan, determine the drinking and irrigation suitability of groundwater: an in-depth risk assessment - Ghazala Mohammad Ali; Muhammad Akhtar; Muhammad Faraz Bhatti; Fazal Adnan; Malik Badshah; Ghayas Haider Sajid; Ghulam Haider (Environmental Geochemistry and Health, 2026)

Facile and Low Cost Synthesis of NiFe-LDH/ZnO Composites for Efficient Photodegradation of MB in Aqueous Solution Under the Illumination of Natural Sunlight - Ramsha Saleem; Humera Shaikh; Muhammad Saajan Barhaam; Qurban Ali Shah; Baradi Waryani; Mazhar Ali Abbasi; Imran Ali Halepoto; Nek Muhammad Shaikh; Muhammad Ali Bhatti; Rafat M. Ibrahim; Elmuez Dawi; Aneela Tahira; et al. (Water, Air, & Soil Pollution, 2026)

Retraction Note: Adenosine protects D-galactose induced alterations in rat model of aging via attenuating neurochemical profile and redox status - Noreen Samad; Arooj Nasir; Muhammad Habib ur Rehman; Sheraz Ahmed Bhatti; Imran Imran (Metabolic Brain Disease, 2026)

Combined effect of different calcination temperatures and non-equilibrium low-pressure plasma on photocatalytic activity of bi-phasic heterostructured CuMoO4-ZrO2/GO composite - Mahwish Iqbal; Tehmeena Ishaq; Muhammad Ahsan Rashid; Mahreen Iqbal; Haq Nawaz Bhatti (Journal of Water Process Engineering, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

Isolation, Characterization, and Modes of Action of Antifungal Compounds from Rhizomes of Dryopteris nigropaleacea - Faisal I. Jafri; Muhammad Akbar; Yasir Nazir; Amna Khalil; Khizar H. Bhatti; Anna Andolfi; Muhammad W. Mazhar; Shoaib Ashiq (Current Microbiology, 2026)

Navigating climate policy uncertainty: how innovation and institutional quality drive GHG emissions reduction in G7 countries - Muhammad Asif; Muhammad Azam Zia; Mughair Aslam Bhatti (Clean Technologies and Environmental Policy, 2026)

Green technology, digital transformation, and energy efficiency: driving carbon reduction and waste management innovation in G20 Countries - Muhammad Asif; Muhammad Azam Zia; Muhammad Hashim; Uzair Aslam Bhatti (Clean Technologies and Environmental Policy, 2025)

Evaluating soil health and aggregation potential in dryland soils under diverse land uses in semiarid Pakistan - Abdul Wahab; Kashif Ali Kubar; Muhammad Shaaban; Zia-ul-hassan; Inayatullah Rajpar; Allah Wadhayo Gandahi; Saleem Maseeh Bhatti; Muhammad Afzal Chhajro; Qambar Baloch (Environmental Monitoring and Assessment, 2025)

Impacting Value of Different Oxidation States of Copper and Jamun Leaves Extract During the Green Synthesis of CuO Nanostructures for Efficient Photocatalytic Degradation of Methylene Blue in Aqueous Solutions - Saira Bughio; Muhammad Ali Bhatti; Sajida Bughio; Aneela Tahira; Tayyaba Khalid; Ghulam Zuhra Memon; Muhktiar Hussain Bozdar; Elmuez Dawi; Ayman Nafady; Matteo Tonezzer; Zafar Hussain Ibupoto (Water, Air, & Soil Pollution, 2025)

Efficacy and Safety of Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease: An Updated Meta-Analysis of Randomized Controlled Trials - Iftikhar Khan; Umama Rehman; Fatima Aslam; Saad Khan; Umna Bhatti; Hussain Ramzan; Fatima Naveed; Javeria Nawaz; Syeda Malaika Raza; Kiran Inam; Faiza Rajput; Syed Muhammad Seyab; et al. (Stem Cell Reviews and Reports, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Predicting ambient PM2.5 levels in the Yangtze River Delta with random forest algorithms: A machine learning approach - Ahmad Hasnain; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Basit Nadeem; Geng Wei; Waqas Akram Cheema; Muhammad Asif (Environment, Development and Sustainability, 2025)

Antimony-doped NASICON-type solid electrolyte with homogeneous sodium-ion flux for high-temperature solid-state sodium batteries - Muhammad Akbar; Iqra Moeez; Ali Hussain Umar Bhatti; Young Hwan Kim; Mingony Kim; Ji-Young Kim; Jiwon Jeong; Jae Ho Park; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Synthesis and optimization of silver-modified BiOCl/CuBi2O4 heterostructure composite as an efficient visible light photocatalyst against reactive green 5 and turquoise blue dyes - Raheeba Akbar; Haq Nawaz Bhatti; Muhammad Zahid; Muhammad Yasin Naz (Environmental Science and Pollution Research, 2025)

Overexpression of StDREB30 Gene Enhances Salt Stress Tolerance in Transgenic Potato - Qurat- Ul Ain-Ali; Faiza Munir; Muhammad Faraz Bhatti; Rabia Amir; Alvina Gul (Potato Research, 2025)

Numerical investigations on RC beam-column structures under collapse phenomenon—a simplified finite element approach - Aleem Ullah; Abdul Qadir Bhatti; Attiq Ur Rahman Dogar; Girum Urgessa; Muhammad Usman (Innovative Infrastructure Solutions, 2025)

Exploring the impact of cold plasma-induced surface oxygen vacancies on charge carrier dynamics in Z-scheme CoMoO6/ZrO2/GO heterojunction for efficiency improvement in photocatalysis - Mahwish Iqbal; Muhammad Ahsan Rashid; Rida Fatima; Mahreen Iqbal; Haq Nawaz Bhatti (Journal of Water Process Engineering, 2025)

Retraction notice to “Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure” [J. Environ. Manag. 356 (2024) 120673] - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Development of a dispersive liquid–liquid microextraction technique for ultra-sensitive detection of gold in environmental samples using atomic absorption spectrometry - Waheed Ali Soomro; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani; Zulfiqar Ali Bhatti; Rafi-u-Zaman Brohi; Imran Khan Rind (Environmental Monitoring and Assessment, 2025)

Comparative Nutritional Profiling of Economically Important Shrimp Species in Pakistan - Muhammad Bhatti; Shahid Sherzada; Sohail Ahmad; Muhammad Qazi; Amina Ayub; Saeed Khan; Muhammad Khan; Iqra Rani; Nimra Hussain; Joanna Nowosad; Dariusz Kucharczyk (Journal of Marine Science and Engineering, 2025)
Shrimp are widely recognized as a nutritious and flavorful food choice due to their tender and delicious meat. This study evaluated the nutritional composition of three economically important shrimp species: Penaeus merguiensis, Penaeus monodon, and Penaeus indicus, collected from the coastal areas of Pakistan. All shrimp species were found to be high in protein and low in fat content. The ratio of essential amino acids (EAAs), non-essential amino acids (NEAAs), and total amino acids (TAAs) varied significantly (p ≤ 0.05) among species, with P. indicus showing slightly higher values. Regarding fatty acid analysis, total saturated fatty acid content was found to be 35.04% in P. merguiensis, 52.43% in P. monodon, and 44.77% in P. indicus. Similarly, the polyunsaturated fatty acid content was found to be 26.24%, 26.77%, and 24.74%, in P. merguiensis, P. monodon, and P. indicus, respectively. Based on nutrient yield, P. monodon stands out as the most nutrient-dense species, followed by P. indicus and P. merguiensis. Overall, the present study suggests that all shrimp species can be used as a healthy choice of food and a good source of animal protein for human consumption. These findings provide valuable insights into the role of shrimp in promoting a healthy and balanced diet.

Heavy metals concentration and human health risk assessment in selected shrimp species of Pakistan - Alveena Draz; Muhammad Asghar Qazi; Talib Hussain; Owais Ahmad; Muhammad Mahd Nazir; Muhammad Bilal Bhatti; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

Dendrite-free Sb-doped NASICON-type Na3Zr2Si2PO12 solid-electrolyte for stable solid-state sodium batteries - Muhammad Akbar; Mingony Kim; Iqra Moeez; Ali Hussain Umar Bhatti; Young Hwan Kim; Jiwon Jeong; Ji-Young Kim; Jae-Ho Park; Seungho Yu; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Nanoarchitectonics of molybdenum rich crown shaped polyoxometalates based ionic liquids reinforced on magnetic nanoparticles for the removal of microplastics and heavy metals from water - Hameed Ullah; Taghrid S. Alomar; Muhammad Tariq; Najla AlMasoud; Moazzam H. Bhatti; Muhammad Ajmal; Zahra Nazar; Muhammad Nadeem; Hafiz Muhammad Asif; Muhammad Sohail (Journal of Environmental Chemical Engineering, 2024)

Dietary Chlorella vulgaris mitigates aflatoxin B1 toxicity in broiler chicken: Toxicopathological, hematobiochemical and immunological perspectives - Aisha Khatoon; Aneela Amin; Sana Majeed; Shafia Tehseen Gul; Muhammad Imran Arshad; Muhammad Kashif Saleemi; Ashiq Ali; Rao Zahid Abbas; Sheraz Ahmad Bhatti (Toxicon, 2024)

Aflatoxin B1-associated oxidative stress along with toxicopathological and immunological alterations is efficiently counteracted by dietary supplementation of distillery yeast sludge in broilers - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Muhammad Kashif Saleemi; Halis Oguz; Shafia Tehseen Gul; Rao Zahid Abbas; Ashiq Ali; Sheraz Ahmad Bhatti (Mycotoxin Research, 2024)

Evaluating the biological activity of rolB-transgenic Nicotiana tabacum plants using phytochemical and pharmacological approaches - Afshan Anwar; Shabana Haneef; Hammad Ismail; Muhammad Zeeshan Bhatti; Nazif Ullah; Iram Murtaza; Bushra Mirza (Plant Biosystems, 2024)

Field validation of NDVI to identify crop phenological signatures - Muhammad Tousif Bhatti; Hammad Gilani; Muhammad Ashraf; Muhammad Shahid Iqbal; Sarfraz Munir (Precision Agriculture, 2024)
Purpose and Methods Crop identification using remotely sensed imagery provides useful information to make management decisions about land use and crop health. This research used phonecams to acquire the Normalized Difference Vegetation Index (NDVI) of various crops for three crop seasons. NDVI time series from Sentinel (L121-L192) images was also acquired using Google Earth Engine (GEE) for the same period. The resolution of satellite data is low therefore gap filling and smoothening filters were applied to the time series data. The comparison of data from satellite images and phenocam provides useful insight into crop phenology. The results show that NDVI is generally underestimated when compared to phenocam data. The Savitzky-Golay (SG) and some other gap filling and smoothening methods are applied to NDVI time series based on satellite images. The smoothened NDVI curves are statistically compared with daily NDVI series based on phenocam images as a reference. Results The SG method has performed better than other methods like moving average. Furthermore, polynomial order has been found to be the most sensitive parameter in applying SG filter in GEE. Sentinel (L121-L192) image was used to identify wheat during the year 2022–2023 in Sargodha district where experimental fields were located. The Random Forest Machine Leaning algorithm was used in GEE as a classifier. Conclusion The classification accuracy has been found 97% using this algorithm which suggests its usefulness in applying to other areas with similar agro-climatic characteristics.

Characterization of two novel fusariviruses co-infecting a single isolate of phytopathogenic fungus Botrytis cinerea - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Nasar Virk; Muhammad Faraz Bhatti (Virus Genes, 2024)

Hyperspectral target detection using self-supervised background learning - Muhammad Khizer Ali; Benish Amin; Abdur Rahman Maud; Farrukh Aziz Bhatti; Komal Nain Sukhia; Khurram Khurshid (Advances in Space Research, 2024)

Effect of hydraulic retention time on wastewater treatment and microalgal growth at low light intensity - Ramsha Malik; Sahar Saleem; Muhammad Basharat; Muhammad Faraz Bhatti; Zeshan Sheikh (Algal Research, 2024)

Multiple Transgenic Strategies Positively Regulate Cold-Induced Sweetening in Low Temperature Stored Potato Tubers - Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Shazia Shafique; Nusrat Jahan; Muhammad Umar Bhatti; Rida Khalid; Ayman Naeem; Qamar Abbas; Sobiya Shafique; Bushra Tabassum (Potato Research, 2024)

Predicting ambient PM2.5 concentrations via time series models in Anhui Province, China - Ahmad Hasnain; Muhammad Zaffar Hashmi; Sohaib Khan; Uzair Aslam Bhatti; Xiangqiang Min; Yin Yue; Yufeng He; Geng Wei (Environmental Monitoring and Assessment, 2024)

RETRACTED: Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Algae-derived bioactive compounds as potential pharmaceuticals for cancer therapy: A comprehensive review - Lubna Anjum Minhas; Muhammad Kaleem; Hafiz Muhammad Umer Farooqi; Farzana Kausar; Rooma Waqar; Theophilus Bhatti; Shahid Aziz; Dong Won Jung; Abdul Samad Mumtaz (Algal Research, 2024)

Assessing the effectiveness of 3, 4-dimethylpyrazole phosphate (DMPP) inhibitor in mitigating N2O emissions from contrasting Cd-contaminated soils - Muhammad Laeeq Ur Rehman Hashmi; Yasir Hamid; Muhammad Usman; Jipeng Luo; Sangar Khan; Tang Sheng; Nabila Bano; TalhaTufail Bhatti; Tingqiang Li (Science of The Total Environment, 2024)

Green fabrication of copper nano-fertilizer for enhanced crop yield in cowpea cultivar: A sustainable approach - Muhammad Mustafa; Muhammad Azam; Haq Nawaz Bhatti; Amina Khan; Laiba Zafar; Abdul Malik Rehan Abbasi (Biocatalysis and Agricultural Biotechnology, 2024)

Modelling of debris-flow susceptibility and propagation: a case study from Northwest Himalaya - Hamza Daud; Javed Iqbal Tanoli; Sardar Muhammad Asif; Muhammad Qasim; Muhammad Ali; Junaid Khan; Zahid Imran Bhatti; Ishtiaq Ahmad Khan Jadoon (Journal of Mountain Science, 2024)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Investigating the effects of matrix acidizing and acid fracturing on the production optimization of a carbonate reservoir: a case study - Umair Qureshi; Haris Ahmed Qureshi; Amanat Ali Bhatti; Muhammad Salman Saeed; Muhammad Sameer Khalid (Arabian Journal of Geosciences, 2023)

Biochar alleviated the toxic effects of PVC microplastic in a soil-plant system by upregulating soil enzyme activities and microbial abundance - Attia Rubab Khalid; Tariq Shah; Muhammad Asad; Ahmad Ali; Eisha Samee; Fazal Adnan; Muhammad Faraz Bhatti; Sven Marhan; Claudia I. Kammann; Ghulam Haider (Environmental Pollution, 2023)

The presence of mycoviral infection attenuates the growth and pathogenicity of the phytopathogenic fungus Botrytis cinerea collected from strawberry fields in Pakistan - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Danish Ilyas Baig; Tehsin Fatma; Nasar Virk; Muhammad Faraz Bhatti (European Journal of Plant Pathology, 2023)

Mycovirus-induced hypovirulence in notorious fungi Sclerotinia: a comprehensive review - Haris Ahmed Khan; Mamuna Mukhtar; Muhammad Faraz Bhatti (Brazilian Journal of Microbiology, 2023)

ADU-Net: Semantic segmentation of satellite imagery for land cover classification - Muhammad Talha; Farrukh A. Bhatti; Sajid Ghuffar; Hamza Zafar (Advances in Space Research, 2023)

Enhancement in anaerobic biogas conversion by visible light photocatalytic Pre-treatment of rice husk with indium vanadate decorated titanium dioxide nanocomposite - Jamshaid Rashid; Talha Tufail Bhatti; Muhammad Hassan; M.A. Barakat; Rajeev Kumar; Ming Xu (Fuel, 2023)

Morphological and molecular observations of nematodes belonging to the family Hoplolaimidae from the Thar Desert, Pakistan - Ramzan Ali; Ebrahim Shokoohi; Erum Iqbal; Muhammad Ismail Bhatti; Saboohi Raza (Biologia, 2023)

Segmentation of digital rock images using texture analysis and deep network - Shahzad Manzoor; Tehreem Qasim; Naeem Bhatti; Muhammad Zia (Arabian Journal of Geosciences, 2023)

Numerical investigation of thermal-hydraulic design of a printed circuit steam generator - Muhammad Ali Khan; Syed Anas Sohail; Khalid Waheed; Waseem Siddique; Muhammad Ilyas; Fatih Aydogan; Kamran Rasheed Qureshi; Imran Shaban Bhatti (Annals of Nuclear Energy, 2023)

Transgenic maize inbred lines expressing high levels of Bacillus thuringiensis vegetative insecticidal protein (Vip3Aa86) offer effective control of maize stem borer (Chilo partellus) - Muhammad Umar Bhatti; Bushra Tabassum; Colin Berry; Anwar Khan; Uzma Qaisar; Ejaz Ali; Rida Khalid; Abdul Munim Farooq; Muhammad Tariq; Hasan Ayaz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Assessing the ambient air quality patterns associated to the COVID-19 outbreak in the Yangtze River Delta: A random forest approach - Ahmad Hasnain; Yehua Sheng; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Zulkifl Ahmed; Yong Zha (Chemosphere, 2023)

Production performance, protein digestibility, gut health and economic efficiency in sexed broilers with super dozing of lysine - Najam us Sahar; Muhammad Shoaib; Muhammad Aslam Mirza; Shaukat Ali Bhatti; Shahzad Ashraf; Noreen Aslam; Alishbah Roobi; Muhammad Arslan Asif (Tropical Animal Health and Production, 2023)

Biocatalytic degradation of reactive blue 221 and direct blue 297 dyes by horseradish peroxidase immobilized on iron oxide nanoparticles with improved kinetic and thermodynamic characteristics - Umme Kalsoom; Nasira Khalid; Affaf Ibrahim; Syed Salman Ashraf; Haq Nawaz Bhatti; Zainab Ahsan; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Genome mining, antimicrobial and plant growth-promoting potentials of halotolerant Bacillus paralicheniformis ES-1 isolated from salt mine - Sajid Iqbal; Muhammad Qasim; Hazir Rahman; Naeem Khan; Rehan Zafar Paracha; Muhammad Faraz Bhatti; Aneela Javed; Hussnain Ahmed Janjua (Molecular Genetics and Genomics, 2023)

Identification of novel totiviruses from the ascomycetous fungus Geotrichum candidum - Haris Ahmed Khan; Hideki Kondo; Sabitree Shahi; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2022)

Evaluation and projection of precipitation in Pakistan using the Coupled Model Intercomparison Project Phase 6 model simulations - Adnan Abbas; Safi Ullah; Waheed Ullah; Muhammad Waseem; Xin Dou; Chengyi Zhao; Aisha Karim; Jianting Zhu; Daniel Fiifi Tawia Hagan; Asher Samuel Bhatti; Gohar Ali (International Journal of Climatology, 2022)
This study aimed to evaluate the performance of global climate models (GCMs) from the family of the Coupled Model Intercomparison Project Phase 6 (CMIP6) in the historical simulation of precipitation and select the best performing GCMs for future projection of precipitation in Pakistan under multiple shared socioeconomic pathways (SSPs). The spatiotemporal performance of GCMs was evaluated against the Climate Research Unit (CRU) data in simulating annual precipitation during 1951–2014, using the Taylor diagram and interannual variability skill (IVS). Moreover, the modified Mann–Kendall (mMK) and Sen's slope estimator (SSE) tests were employed to estimate significant trends in future precipitation for the period 2015–2100. Based on the comprehensive ranking index (CRI), the HadGEM3‐GC31‐MM model has the highest skill in simulating precipitation distributions followed by EC‐Earth3‐Veg‐LR, CNRM‐ESM2‐1, MPI‐ESM1‐2‐HR, CNRM‐CM6‐1, MRI‐ESM2‐0, CNRM‐CM6‐1‐HR, EC‐Earth3‐Veg, MCM‐UA‐1‐0, INM‐CM5‐0, KACE‐1‐0‐G, CAMS‐CSM1‐0, and HadGEM3‐GC31‐LL models. Furthermore, the projections of the best models ensemble mean (BMEM) showed that the study region will experience a substantial increase in precipitation under SSP3‐7.0 and SSP5‐8.5 but an indolent rise under SSP1‐2.6 and SSP2‐4.5 scenarios. The summer and annual precipitations exhibit a statistically significant increasing trend relative to the winter season under most scenarios. Moreover, the magnitude of monotonic trends in seasonal and annual precipitation progresses from low forcing scenario (SSP1‐2.6) to high forcing scenario (SSP5‐8.5). The findings of the study could provide a benchmark in selecting appropriate GCMs for future projection over a data scare region, like Pakistan. Moreover, the projected trends of future precipitation are crucial in devising adaption and mitigation actions towards sustainable planning of water resource management, food security, and disaster risk management.

Dirty versus clean fuel for cooking in Pakistan: regional mapping and correlates - Tusawar Iftikhar Ahmad; Muhammad Atif Nawaz; Kokab Kiran; Vishal Dagar; Muhammad Azhar Bhatti; Altaf Hussain (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Adenosine protects D-galactose induced alterations in rat model of aging via attenuating neurochemical profile and redox status - Noreen Samad; Arooj Nasir; Muhammad Habib ur Rehman; Sheraz Ahmed Bhatti; Imran Imran (Metabolic Brain Disease, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

A novel victorivirus from the phytopathogenic fungus Neofusicoccum parvum - Haris Ahmed Khan; Yukiyo Sato; Hideki Kondo; Atif Jamal; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2022)

Inhibitory Effects of Selenium on Arsenic-Induced Anxiety-/Depression-Like Behavior and Memory Impairment - Noreen Samad; Tazeen Rao; Muhammad Habib ur Rehman; Sheraz Ahmed Bhatti; Imran Imran (Biological Trace Element Research, 2022)

Fabrication of visible light active Mn-doped Bi2WO6-GO/MoS2 heterostructure for enhanced photocatalytic degradation of methylene blue - Noor Tahir; Muhammad Zahid; Ijaz Ahmad Bhatti; Yasir Jamil (Environmental Science and Pollution Research, 2022)

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

A second capsidless hadakavirus strain with 10 positive-sense single-stranded RNA genomic segments from Fusarium nygamai - Haris Ahmed Khan; Yukiyo Sato; Hideki Kondo; Atif Jamal; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2021)

Combating immunotoxicity of aflatoxin B1 by dietary carbon supplementation in broiler chickens - Sheraz Ahmed Bhatti; Muhammad Zargham Khan; Muhammad Kashif Saleemi; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2021)

Parameter estimation of the Pareto distribution using least squares approaches blended with different rank methods and its applications in modeling natural catastrophes - Shahzad Hussain; Sajjad Haider Bhatti; Tanvir Ahmad; Muhammad Ahmed Shehzad (Natural Hazards, 2021)

A technological innovation and economic progress enhancement: an assessment of sustainable economic and environmental management - Wu Hao; Farhat Rasul; Zobia Bhatti; Muhammad Shahid Hassan; Ishtiaq Ahmed; Nabila Asghar (Environmental Science and Pollution Research, 2021)

Effect of milk or milk replacer offered at varying levels on growth performance of Friesian veal calves - Muhammad Khalid Qadeer; Shaukat Ali Bhatti; Haq Nawaz; Muhammad Sajjad Khan (Tropical Animal Health and Production, 2021)

Elucidation of larvicidal potential of metallic and environment friendly food-grade nanostructures against Aedes albopictus - Toqeer Ahmed; Irfan Liaqat; Muhammad Zeeshan Hyder; Shaheen Akhtar; Assad Hafeez Bhatti; Shahid Bilal Butt; Zahid Imran; Tayyaba Yasmin; Shabbar Abbas (Environmental Geochemistry and Health, 2021)

Experimental investigations of arsenic adsorption from contaminated water using chemically activated hematite (Fe2O3) iron ore - Abdul Qayoom Memon; Shoaib Ahmed; Zulfiqar Ali Bhatti; Ghulamullah Maitlo; Abdul Karim Shah; Shaukat Ali Mazari; Atta Muhammad; Abdul Sattar Jatoi; Ghulam Abbas Kandhro (Environmental Science and Pollution Research, 2021)

Barbecued desi chicken: an investigation on the impact of polluted milieu upon formation and ingestion of polycyclic aromatic hydrocarbons (PAHs) in commercial versus laboratory barbecued organs along with stochastic cancer risk assessments in people from an industrial district of Punjab, Pakistan - Zunaira Mubeen; Ijaz Ahmad Bhatti; Haq Nawaz Bhatti; Muhammad Asghar (Environmental Science and Pollution Research, 2021)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Effect of increasing pre-pubertal concentrate levels on reproductive and lactation performance of Nili-Ravi Buffalo heifers - Muhammad Saadullah; Zeeshan Muhammad Iqbal; Muhammad Naveed-ul-Haque; Hifzulrahman; Jalees Ahmed Bhatti; Muhammad Abdullah (Tropical Animal Health and Production, 2020)

Advances in exogenous RNA delivery techniques for RNAi-mediated pest control - Olawale Samuel Adeyinka; Saman Riaz; Nida Toufiq; Iqra Yousaf; Muhammad Umar Bhatti; Anicet Batcho; Amos Afolarin Olajide; Idrees Ahmad Nasir; Bushra Tabassum (Molecular Biology Reports, 2020)

Effect of fans and showers on the physiological measures and reproductive performance of Holstein Friesian bulls during subtropical summer - Mahboob Ahmed Butt; Jalees Ahmed Bhatti; Anjum Khalique; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2020)

Type 1 Fimbriae and Motility Play a Pivotal Role During Interactions of Salmonella typhimurium with Acanthamoeba castellanii (T4 Genotype) - Talha Mannan; Muhammad Wasim Rafique; Muhammad Haroon Bhatti; Abdul Matin; Irfan Ahmad (Current Microbiology, 2020)

Resistance to Chilo infuscatellus (Lepidoptera: Pyraloidea) in transgenic lines of sugarcane expressing Bacillus thuringiensis derived Vip3A protein - Saman Riaz; Idrees Ahmad Nasir; Muhammad Umar Bhatti; Olawale Samuel Adeyinka; Nida Toufiq; Iqra Yousaf; Bushra Tabassum (Molecular Biology Reports, 2020)

Reservoir Inflow Prediction by Ensembling Wavelet and Bootstrap Techniques to Multiple Linear Regression Model - Adnan Bashir; Muhammad Ahmed Shehzad; Ijaz Hussain; Muhammad Ishaq Asif Rehmani; Sajjad Haider Bhatti (Water Resources Management, 2019)

Future water demand modeling using water evaluation and planning: a case study of the Indus Basin in Pakistan - Daniyal Hassan; Muhammad Naseer Rais; Waqas Ahmed; Rakhshinda Bano; Steven J. Burian; Muhammad Wajid Ijaz; Faris Ahmed Bhatti (Sustainable Water Resources Management, 2019)

Effect of fat supplementation on physiological and reproductive performance of Holstein Friesian bulls during summer - Mahboob Ahmed Butt; Jalees Ahmed Bhatti; Anjum Khalique; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2019)

Correction to: Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Amelioration of toxicopathological effects of cadmium with silymarin and milk thistle in male Japanese quail (Coturnix japonica) - Muhammad Kashif Saleemi; Muhammad Waseem Tahir; Rao Zahid Abbas; Masood Akhtar; Aamir Ali; Muhammad Tariq Javed; Zahida Fatima; Muhammad Zubair; Sheraz Ahmed Bhatti; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2019)

Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Different ambient management intervention techniques and their effect on milk production and physiological parameters of lactating NiliRavi buffaloes during hot dry summer of subtropical region - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Rahman Ullah; Qurat ul Ain; Muhammad Sajid Hasni; Mahboob Ali; Abdul Rashid; Imran Qaisar; Ghazunfar Rashid; Rafi Uddin (Tropical Animal Health and Production, 2019)

Climate change evidence and community level autonomous adaptation measures in a canal irrigated agriculture system of Pakistan - Muhammad Tousif Bhatti; Waqas Ahmad; Muhammad Azeem Shah; Muhammad Shahzad Khattak (Climate and Development, 2019)

Factors hindering the implementation of surgical site infection control guidelines in the operating rooms of low-income countries: a mixed-method study - Muhammad Nasir Ayub Khan; Daniëlle M. L. Verstegen; Abu Bakar Hafeez Bhatti; Diana H. J. M Dolmans; Walther Nicolaas Anton van Mook (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effect of ambient management interventions on the production and physiological performance of lactating Sahiwal cattle during hot dry summer - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Khalid Javed; Mehboob Ali; Ghazanfar Rashid; Rafi Uddin; Ali Hassan Badini; Mudassar Jehan (Tropical Animal Health and Production, 2018)

Effects of anthropogenic nitrogen deposition on soil nitrogen mineralization and immobilization in grassland soil under semiarid climatic conditions - Ambreen Bhatti; Jawad Ahmad; Muhammad Qasim; Muhammad Riaz; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2018)

Effects of feeding bentonite clay upon ochratoxin A–induced immunosuppression in broiler chicks - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Sheraz Ahmed Bhatti (Food Additives & Contaminants: Part A, 2018)

Immunomodulatory and therapeutic role of Cinnamomum verum extracts in collagen-induced arthritic BALB/c mice - Mirza Muhammad Fahd Qadir; Attya Bhatti; Muhammad Usman Ashraf; Mansur Abdullah Sandhu; Sidrah Anjum; Peter John (Inflammopharmacology, 2018)

Characterization of a salt resistant bacterial strain Proteus sp. NA6 capable of decolorizing reactive dyes in presence of multi-metal stress - Naila Abbas; Sabir Hussain; Farrukh Azeem; Tanvir Shahzad; Sajjad Haider Bhatti; Muhammad Imran; Zulfiqar Ahmad; Zahid Maqbool; Muhammad Abid (World Journal of Microbiology and Biotechnology, 2016)

The potential of precision surface irrigation in the Indus Basin Irrigation System - Arif A. Anwar; Waqas Ahmad; Muhammad Tousif Bhatti; Zia Ul Haq (Irrigation Science, 2016)

River bank erosion and channel evolution in sand-bed braided reach of River Chenab: role of floods during different flow regimes - Muhammad Ashraf; Muhammad Tousif Bhatti; Abdul Sattar Shakir (Arabian Journal of Geosciences, 2016)

Bioanalytical evaluation of Cinnamomum zeylanicum essential oil - Muhammad Saleem; Haq Nawaz Bhatti; Muhammad Idrees Jilani; Muhammad Asif Hanif (Natural Product Research, 2015)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Identification of a homozygous splice site mutation in the dynein axonemal light chain 4 gene on 22q13.1 in a large consanguineous family from Pakistan with congenital mirror movement disorder - Iltaf Ahmed; Kirti Mittal; Taimoor I. Sheikh; Nasim Vasli; Muhammad Arshad Rafiq; Anna Mikhailov; Mehrnaz Ohadi; Huda Mahmood; Guy A. Rouleau; Attya Bhatti; Muhammad Ayub; Myriam Srour; et al. (Human Genetics, 2014)

Antibacterial Efficacy of Silver Nanoparticles Synthesized by a Green Method Using Bark Extract of Melia azedarach L - Ansar Mehmood; Ghulam Murtaza; Tariq Mahmood Bhatti; Muhammad Raffi; Rehana Kausar (Journal of Pharmaceutical Innovation, 2014)

A Question Mark on Zinc Deficiency in 185 Million People in Pakistan—Possible Way Out - Nauman Khalid; Anwaar Ahmed; Muhammad Shahbaz Bhatti; Muhammad Atif Randhawa; Asif Ahmad; Rabab Rafaqat (Critical Reviews in Food Science and Nutrition, 2014)

Perspective of Surface Active Agents in Baking Industry: An Overview - Asif Ahmad; Nazish Arshad; Zaheer Ahmed; Muhammad Shahbaz Bhatti; Tahir Zahoor; Nomana Anjum; Hajra Ahmad; Asma Afreen (Critical Reviews in Food Science and Nutrition, 2014)

A novel dsRNA element isolated from the Aspergillus foetidus mycovirus complex - Zisis Kozlakidis; Noemi Herrero; Selin Ozkan; Muhammad F. Bhatti; Robert H. A. Coutts (Archives of Virology, 2013)

Absorption and Fluorescence Emission Attributes of a Fluorescent dye: 2,3,5,6-Tetracyano-p-Hydroquinone - Muhammad Zahid; Günter Grampp; Asim Mansha; Ijaz Ahmad Bhatti; Sadia Asim (Journal of Fluorescence, 2013)

Prospects of raising Sahiwal cow calves for veal production under tropical environment - Shaukat Ali Bhatti; Kamran Nazir; Muhammad Jamil Basra; Muhammad Sajjad Khan; Muhammad Sarwar; Muhammad Ashraf Iqbal Mughal (Tropical Animal Health and Production, 2013)

Sequence determination of a quadripartite dsRNA virus isolated from Aspergillus foetidus - Zisis Kozlakidis; Noemi Herrero; Selin Ozkan; Lakkhana Kanhayuwa; Atif Jamal; Muhammad F. Bhatti; Robert H. A. Coutts (Archives of Virology, 2013)

Breast Cancer Proteome Takes More Than Two to Tango on TRAIL: Beat Them at Their Own Game - Ammad Ahmad Farooqi; Sundas Fayyaz; Muhammad Tahir; Muhammed Javed Iqbal; Shahzad Bhatti (The Journal of Membrane Biology, 2012)

Incidence of dsRNA Mycoviruses in a Collection of Aspergillus fumigatus Isolates - Muhammad F. Bhatti; Atif Jamal; Elaine M. Bignell; Michael A. Petrou; Robert H. A. Coutts (Mycopathologia, 2012)

Effect of diet on preweaning performance of Sahiwal calves - Shaukat Ali Bhatti; Muhammad Faisal Ahmed; Peter Charles Wynn; David McGill; Muhammad Sarwar; Muhammd Afzal; Ehsan Ullah; Musarrat Abbas Khan; Muhammad Sajjad Khan; Russell Bush; Hassan Mahmood Warriach; Ahrar Khan (Tropical Animal Health and Production, 2012)

NutriTRAILomics in prostate cancer: time to have two strings to one’s bow - Ammad Ahmad Farooqi; Aamir Rana; Asma M. Riaz; Ammara Khan; Muhammad Ali; Sara Javed; Shahzeray Mukhtar; Sehrish Minhaj; Javeria Rafique Rao; Javairia Rajpoot; Rafia Amber; Fiza Asif Javed; et al. (Molecular Biology Reports, 2012)

Complete nucleotide sequences of two dsRNAs associated with a new partitivirus infecting Aspergillus fumigatus - Muhammad Faraz Bhatti; Elaine M. Bignell; Robert H. A. Coutts (Archives of Virology, 2011)

Comparing aflatoxin contamination in chilies from Punjab, Pakistan produced in summer and winter - Shahzad Zafar Iqbal; R. Russell M. Paterson; Ijaz A. Bhatti; Muhammad R. Asi (Mycotoxin Research, 2011)

Assessment of water quality of a river using an indexing approach during the low‐flow season - Muhammad Tousif Bhatti; Muhammad Latif (Irrigation and Drainage, 2011)
The River Chenab is one of the largest rivers in Pakistan with an average annual flow of 5.29 billion cubic metres (BCM). The river traverses a total length of 576 km through a number of densely populated and industrial cities in the Punjab province of Pakistan. In the present study, a segment of 292 km was monitored for a variety of cardinal water quality constituents during the low‐flow months of 2006–07 and 2007–08. Water quality indices (WQIs) were calculated for three uses of the river water, i.e. irrigation, drinking and aquatic life, using the CWQI 1.0 model developed by the task group of the Canadian Council of Ministers of the Environment (CCME). The results revealed that the lower river reach (185–233 km) was more polluted than the upper 185 km segment. In this river reach, overall WQI ranking was poor for drinking and marginal for both irrigation and aquatic life. The WQIs for all three uses were ranked poor at the sampling station located at 233 km along the river. Copyright © 2009 John Wiley & Sons, Ltd.

Transfer of radioactivity from soil to vegetation in Rechna Doab, Pakistan - Abdul Jabbar; Muhammad Tufail; Waheed Arshed; Arshed Salem Bhatti; Syed Salman Ahmad; Perveen Akhter; Muhammad Dilband (Isotopes in Environmental and Health Studies, 2010)

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan - Abdul Jabbar; Waheed Arshed; Arshad Saleem Bhatti; Syed Salman Ahmad; Perveen Akhter; Saeed -Ur -Rehman; Muhammad Iftikhar Anjum (Environmental Monitoring and Assessment, 2010)

Aflatoxin B1 in chilies from the Punjab region, Pakistan - Shahzad Z. Iqbal; R. Russell M. Paterson; Ijaz A. Bhatti; Muhammad R. Asi; Munir A. Sheikh; Haq N. Bhatti (Mycotoxin Research, 2010)

Recent developments in biodegradation of industrial pollutants by white rot fungi and their enzyme system - Muhammad Asgher; Haq Nawaz Bhatti; Muhammad Ashraf; Raymond L. Legge (Biodegradation, 2008)

Kinetic and Equilibrium Modeling for Cr(III) and Cr(VI) Removal from Aqueous Solutions by Citrus reticulata Waste Biomass - Ammara Zubair; Haq Nawaz Bhatti; Muhammad Asif Hanif; Faiza Shafqat (Water, Air, & Soil Pollution, 2008)

Decolorization potential of mixed microbial consortia for reactive and disperse textile dyestuffs - Muhammad Asgher; H. N. Bhatti; S. A. H. Shah; M. Javaid Asad; R. L. Legge (Biodegradation, 2007)

Hyperactivation and thermostabilization of Phanerochaete chrysosporium lignin peroxidase by immobilization in xerogels - Muhammad Asgher; M. Javaid Asad; Haq Nawaz Bhatti; Raymond L. Legge (World Journal of Microbiology and Biotechnology, 2007)